Cover Image. Issue 10 (29th September 2020) - Yamato, Shigeru; Kurematsu, Ayako; Amano, Tomofumi; Ariga, Hajime; Ando, Tetsuya; Komaki, Gen; Wada, Keiji
Abstract : The cover image is based on the Original Article Urocortin 1: A putative excitatory neurotransmitter in the enteric nervous system by Shigeru Yamato et al., https://doi.org/10.1111/nmo.13842